The Impact of Financing Profit Sharing Ratio, Murabahah, and Non-Performing Finance on the Performance of Islamic Banks in Indonesia - Lia Agustina; Mohamad Irsyad (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This research centers on the impact of Profit Sharing Ratio scheme, murabaha financing, and Non-Performing Finance (NPF) on the financial performance of Islamic banks in Indonesia, specifically focusing on the Return on Assets (ROA) metric. Utilizing a quantitative methodology, data from 12 Islamic Commercial Banks from 2014-2023 is analyzed using multiple linear regression techniques with EViews 10 software. The findings show that the Profit Sharing Ratio has no significant effect on the Return on Assets of Islamic Commercial Banks. Although Profit Sharing Ratio is a factor that can reflect the profit sharing between banks and customers, this finding indicates that the volatility of profit sharing schemes does not directly affect the profitability of banks, which could be due to the volatile and uncertain nature of the Islamic market itself. On the other hand, murabaha financing shows a significant effect on Return on Assets, indicating that fixed-margin financing is more effective in increasing bank profitability. Murabaha financing, which is based on the principle of sale and purchase with a clear margin, provides stability and predictability in cash flows, which is important in managing the financial performance of Islamic banks, compared to profit-sharing-based financing products that depend on market fluctuations. In addition, Non-Performing Finance has a significant impact on the financial performance of banks. High Non-Performing Finance indicates a high risk of non-performing financing, which can reduce profits and strain the financial stability of the bank. Hence, improved risk management is essential for Islamic banks to stay profitable and financially healthy.